Peer Effects on Obesity in a Sample of European Children - Wencke Gwozdz; Alfonso Sousa-Poza; Lucia A. Reisch; Karin Bammann; Gabriele Eiben; Yiannis Kourides; Eva Kovács; Fabio Lauria; Kenn Konstabel; Alba M. Santaliestra-Pasias; Krishna Vyncke; Iris Pigeot (Institute for the Study of Labor (IZA), 2015)
This study analyzes peer effects on childhood obesity using data from the first two waves of the IDEFICS study, which applies several anthropometric and other measures of fatness to approximately 14,000 children aged two to nine participating in both waves in 16 regions of eight European countries. Peers are defined as same-sex children in the same school and age group. The results show that peer effects do exist in this European sample but that they differ among both regions and different fatness measures. Peer effects are larger in Spain, Italy, and Cyprus the more collectivist regions in our sample while waist circumference generally gives rise to larger peer effects than BMI. We also provide evidence that parental misperceptions of their own children's weight goes hand in hand with fatter peer groups, supporting the notion that in making such assessments, parents compare their children's weight with that of friends and schoolmates.
Keywords: I12; J13; J22; 330; peer effects; children; obesity; Europe